Water balance and erosivity in the microregions of the State of Paraíba, Brazil - França, Manoel Vieira de (2020)
The objective is to gauge the water classes by the circle of the future climatic scenario of rain and thermal air, taking into account the average monthly scenarios with 10% rainfall reduction and 1 ºC thermal increase (optimistic scenario = B2) and 20% and 4 ºC (pessimistic scenario = A2) and its erosive impact on the soil, aiming to show the effects of global warming by computing the water balance and alerting the population about the soil degradation in the studied areas. The monthly and annual precipitations were acquired from the Northeast Development Superintendence between 1912 to 2018, the thermal data were generated by the Estima-T Software, for the same period under study. To determine the erosivity factor, the equation proposed by Wischmeier and Smith was applied. The evapotranspirative indices registered an increase in the studied regions and scenarios; the evaporative power kept in reductions in scenarios B2 and A2, the deficiencies and the surplus of water registered variations of ups and downs for the scenarios. In scenarios B2 and A2, erosive reductions were recorded in the studied regions, meaning that the topsoil was practically carried and became more compact. The results show that in scenarios B2 and A2, they indicate critical situations of soil conditions which will cause impacts on water resources and rainfed crops.